Integrated clinicopathologic and molecular analysis of endometrial carcinoma: Prognostic impact of the new ESGO-ESTRO-ESP endometrial cancer risk classification and proposal of histopathologic algorithm for its implementation in clinical practice - de Biase, Dario; Maloberti, Thais; Corradini, Angelo Gianluca; Rosini, Francesca; Grillini, Marco; Ruscelli, Martina; Coluccelli, Sara; Altimari, Annalisa; Gruppioni, Elisa; Sanza, Viviana; Turchetti, Daniela; Galuppi, Andrea; et al. (Frontiers in Medicine, 2023)
Introduction: The European Society of Gynecologic Oncology/European Society of Radiation Therapy and Oncology/European Society of Pathology (ESGO/ESTRO/ESP) committee recently proposed a new risk stratification system for endometrial carcinoma (EC) patients that incorporates clinicopathological and molecular features. The aim of the study is to compare the new ESGO/ESTRO/ESP risk classification system with the previous 2016 recommendations, evaluating the impact of molecular classification and defining a new algorithm for selecting cases for molecular analysis to assign the appropriate risk class. Methods: The cohort included 211 consecutive EC patients. Immunohistochemistry and Next-generation sequencing were used to assign molecular subgroups of EC: POLE mutant (POLE), mismatch repair deficient (MMRd), p53 mutant (p53abn), and no specific molecular profile (NSMP). Results: Immuno-molecular analysis was successful in all cases, identifying the four molecular subgroups: 7.6% POLE, 32.2% MMRd, 20.9% p53abn, and 39.3% NSMP. The recent 2020 guidelines showed a 32.7% risk group change compared with the previous 2016 classification system: the reassignment is due to POLE mutations, abnormal p53 expression, and a better definition of lymphovascular space invasion. The 2020 system assigns more patients to lower-risk groups (42.2%) than the 2016 recommendation (25.6%). Considering the 2020 risk classification system that includes the difference between "unknown molecular classification" and "known", the integration of molecular subgroups allowed 6.6% of patients to be recategorized into a different risk class. In addition, the use of the proposed algorithm based on histopathological parameters would have resulted in a 62.6% reduction in molecular analysis, compared with applying molecular classification to all patients. Conclusions: Application of the new 2020 risk classification integrating clinicopathologic and molecular parameters provided more accurate identification of low- and high-risk patients, potentially allowing more specific selection for postoperative adjuvant therapy. The proposed histopathological algorithm decreases the number of tests needed and could be a promising tool for cost reduction without compromising prognostic stratification.